"Partners Not Wage Workers" - شرننة, فرحات (Dirasat in Economics and Business, 1981)
This paper is concerned mainly with the explanation of the principle "Partners not wage workers' It gives some kind of comparison between the partnership system and the wage system. The main points of this paper can be summarized in the following: l. The wage system leads to exploitation because under this system the worker "the producer" receives as wage less than the value of what he had produced. 2. The wage system creates unfair relation- ship between employers and employees. 3. The wage system does not create enough incentives for the workers to produce more since some of the returns does not go back to them. 4.The wage system, if left without interfer- ence will lead to a disequilibrium be- tween aggregate supply and aggregate demand which leads to many economic problems. 5.The best way to create better production relationships is to get rid of the wage system by replacing it with the partnership system, under which will be no exploita-tion and no "surplus value" since the worker will receive exactly his share. Also under the new system the worker will be motivated to work harder to increase the production which means the increase of